2022
DOI: 10.1002/ana.26440
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Retinal Changes in MOGAD

Abstract: Objective Patients with myelin oligodendrocyte glycoprotein antibody (MOG‐IgG)‐associated disease (MOGAD) suffer from severe optic neuritis (ON) leading to retinal neuro‐axonal loss, which can be quantified by optical coherence tomography (OCT). We assessed whether ON‐independent retinal atrophy can be detected in MOGAD. Methods Eighty patients with MOGAD and 139 healthy controls (HCs) were included. OCT data was acquired with (1) Spectralis spectral domain OCT (MOGAD: N = 66 and HCs: N = 103) and (2) Cirrus h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The retina and brain share the same diencephalic origin and have analogous neuronal layers, including a ganglion cell layer (GCL), a retinal nerve fiber layer (RNFL) in addition to a vascular supply [ 7 , 8 ]. Thus, the retina can be highly influenced by pathologies, such as Alzheimer’s disease, migraine, MS, neuromyelitis optica spectrum disorder (NMOSD), and myelin oligodendrocyte glycoprotein-associated disease (MOGAD), which are primarily known to also involve other parts of the CNS [ 9 12 ]. Optic neuritis (ON), characterized by acute visual loss and eye pain, is a common manifestation of MS [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The retina and brain share the same diencephalic origin and have analogous neuronal layers, including a ganglion cell layer (GCL), a retinal nerve fiber layer (RNFL) in addition to a vascular supply [ 7 , 8 ]. Thus, the retina can be highly influenced by pathologies, such as Alzheimer’s disease, migraine, MS, neuromyelitis optica spectrum disorder (NMOSD), and myelin oligodendrocyte glycoprotein-associated disease (MOGAD), which are primarily known to also involve other parts of the CNS [ 9 12 ]. Optic neuritis (ON), characterized by acute visual loss and eye pain, is a common manifestation of MS [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the pRNFL thinning can be obscured by the initial axonal swelling, making it difficult to properly quantify the pRNFL thinning in the first few months after ON attack. Additionally, in comparison with other etiologies of ON, MOGAD-ON might take longer time (12 months vs. 6 months) to resolve from its relatively more extensive optic disc swelling or edema [52].…”
Section: Structural Damagementioning
confidence: 99%
“…A multinational and multicenter retinal imaging study recently reported longitudinal OCT results from 80 MOGAD patients [53]. No progressive GCIPL thinning was observed in MOGAD (in the absence of ON during follow-up) compared to controls.…”
Section: Myelin Oligodendrocyte Glycoprotein Antibody-associated Dise...mentioning
confidence: 99%
“…All NMOSD and HC subjects were recruited as part of the international Collaborative Retrospective Study on retinal OCT in Neuromyelitis Optica (CROCTINO) study and their data were acquired by 13 international centres between 2000 and 2018 (online supplemental table 1). [13][14][15][16] Inclusion criteria were: (1) OCT data acquired by Spectralis SD-OCT devices, (2) the absence of diseases potentially confounding OCT analyses (such as glaucoma, retinal surgery and ametropia >6 D) and (3) the absence of (further) ON attacks within 6 months before the examination date. Clinical data including time since disease onset, time since ON and treatment history were collected at the discretion of each centre.…”
Section: Cohort Designmentioning
confidence: 99%